Legal Framework for Implementation of Trans-fat Regulations in India - Bera, Om P; Aggarwal, Pradeep; Patil, Ashok; Singh, Ranjit; Shah, Vandana (Indian Journal of Community Health, 2023)
Background: The widespread consumption of trans-fats across the world represents a worrying scenario, as it is directly responsible for coronary heart disease and related mortality. Recognizing its dangers, the WHO has set an agenda to eliminate trans-fats by 2023. In India, the Food Safety And Standards Authority ensures safe and wholesome food consumption. In light of the WHO’s standards for the elimination of trans-fats, the FSSAI recently notified limits of trans-fatty acids to not more than 3% in all fats and oils by January 2021 and 2% by January 2022, as well as a limitation on all food products in which edible oils and fats are ingredients to not contain trans-fatty acids of more than 2% mass of total oils/fats in the product by January 2022. Objective: Given the need to eliminate the consumption of trans-fats, it is necessary to assess the implementation of trans-fat regulations in India in order to determine the current status of enforcement and suggest measures for improvement. Methods: Empirical research was conducted through a questionnaire to analyze India’s current status and difficulties in enforcing trans-fat regulations. Results: Although all states have included compliance of trans-fat regulation in the agenda of the State Surveillance Plan but are facing some implementation challenges such as lack of lab infrastructure, lack of trained manpower, unsupportive FBOs, insufficient budget, lack of testing kits, and excluding proprietary food from compliance with trans-fat regulations. Further, all states have felt the need to develop a guideline/manual to facilitate enforcement of the trans-fat regulations. In light of this, the article has critically analyzed the Legal framework for implementing Trans-fat Regulations in India to identify specific implementation challenges due to scattered regulations and recommend suggestive measures for developing the guidelines/manual to facilitate effective implementation of the said regulation.